STUDIES ON THE PREVALENCE OF GASTRO-INTESTINAL NEMATODES IN RUMINANT ANIMALS SLAUGHTERED IN BIU LOCAL GOVERNMENT ABATTOIRS, BORNO STATE, NIGERIA - Alhaji Mohammed, Usman; Fidelis, A. V.; Victor, J. G. (FUDMA JOURNAL OF SCIENCES, 2023)
An epidemiological study was conducted from September-November, 2022 on the prevalence of gastrointestinal nematodes species among naturally infected ruminants slaughtered in Biu Local Area of Borno state, using centrifugal flotation techniques. Out of three hundred and eighty four (384) ruminants (162 goats, 110 sheep and 112 cattle) examined in the three selected abattoirs (Biu, Maringa and Buratai), 239 (62.34%) were infected. Maringa had the prevalence rate of 64.65%, Biu 63.89% and Buratai 63.16%. Although the highest faecal egg counts was recorded in Cattle 66.07%, the difference in prevalence rate between the different location and species of the animal were statistically insignificant p
Keywords: Nematodes; Ruminant Animals; Prevalence; Slaughtered; Biu